PERSONAL DIARY IN PORTUGUESE CLASS: IMPLICATIONS FOR THINKING ABOUT PEDAGOGICAL PRACTICE - Zevoli Peres, Danubia Fernanda [UNESP]; Chaluh, Laura Noemi [UNESP] (Univ Metodista Piracicaba-unimep, 2018)
This work presents a problematized research study by writing in public school and in the academy, developed by a teacher who promoted the writing exercise in personal diaries with 8th grade students. The authors-students and the teacher-researcher's writing and the relations established between them, led to the socio-historical orientation research development evidencing the writing context meaning and the intimacy crossing between these subjects, as friendship. The research also potentiated another data interpretation form, since the teacher-researcher, as author, created chronicles from the students' personal diaries, showing other possibilities of authorship. Finally, it explains that all the movement unleashed in the school brings contributions to rethink pedagogical practices in the Portuguese classes attentive to the teacher's possibility being responsible for the subject authors constitution, as well as writings practice that evidence the authorship marks.
Keywords: Personal diary; Portuguese classroom; Fictionalization; Chronic; Intimacy